2012
DOI: 10.1016/j.acap.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Attention Deficit Hyperactivity Disorder Ambulatory Diagnosis and Medical Treatment in the United States, 2000–2010

Abstract: Objectives Because of several recent clinical and regulatory changes regarding Attention Deficit Hyperactivity Disorder (ADHD) in the United States, we quantified changes in ADHD diagnosis and medication management from 2000 through 2010. Methods We used the IMS Health National Disease and Therapeutic Index™, a nationally representative audit of office-based providers, to examine aggregate trends among children and adolescents under 18. We also quantified how diagnosis and treatment patterns have evolved bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 20 publications
3
75
0
3
Order By: Relevance
“…[10][11][12][13] Other studies sought to quantify the pediatric mental health care PCPs undertake by analyzing mental health care visits and suggested that PCPs are the providers at more mental health visits than psychiatrists. 14,15 The literature has also explored prescribing patterns of PCPs and psychiatrists, with conflicting results among the studies on which provider type is more likely to prescribe psychotropic medications. 14,16,17 Despite attention to this area of research, no studies have yet used a nationally representative sample to characterize the population of children seen or prescribed medications by PCPs versus other types of mental health providers.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Other studies sought to quantify the pediatric mental health care PCPs undertake by analyzing mental health care visits and suggested that PCPs are the providers at more mental health visits than psychiatrists. 14,15 The literature has also explored prescribing patterns of PCPs and psychiatrists, with conflicting results among the studies on which provider type is more likely to prescribe psychotropic medications. 14,16,17 Despite attention to this area of research, no studies have yet used a nationally representative sample to characterize the population of children seen or prescribed medications by PCPs versus other types of mental health providers.…”
Section: What This Study Addsmentioning
confidence: 99%
“…14,16,17 Despite attention to this area of research, no studies have yet used a nationally representative sample to characterize the population of children seen or prescribed medications by PCPs versus other types of mental health providers. Previous national studies have analyzed pediatric mental health use at the level of visits (and not children), 14 have focused on solely 1 condition, 15 or have used only a subset of children and youth (eg, youth in foster care) in their sample. 3,18 Knowing nationally which children are treated by PCPs and which children are treated by other providers can help estimate how much PCPs are engaged in mental health care.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Most previous research on stimulant use has been limited to specific treatment settings (Garfield et al 2012), payers (Castle et al 2007;Winterstein et al 2008), or geographic regions (Rushton and Whitmire 2001;Zito et al 2007). One analysis of nationally representative household informants estimated that the annual prevalence of any stimulant use was 0.1% for younger children (0-5 years), 5.1% for older children (6-12 years), and 5.1% for adolescents (13-18 years) (Zuvekas and Vitiello 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, stimulant medications are the dominant treatment for ADHD in school-aged children and adolescents (Froehlich et al 2007;Garfield et al 2012). In 2010, stimulants accounted for *5.9% of all prescriptions to children (2-11 years) and 7.6% of prescriptions to adolescents (12-17 years).…”
Section: Introductionmentioning
confidence: 99%
“…It begins in childhood and affects 3%-9% of school-aged children, including 30% of pediatric outpatient referrals (Thompson and Ni Bhrolchain 2013) and 2.5% of adults (Simon et al 2009). Stimulants are the leading medications for ADHD, with a significant growth in their prescription over the last two decades, especially in the United States, raising concerns and critics of overprescription (Garfield et al 2012).…”
Section: Introductionmentioning
confidence: 99%